Stepping Up Early Childhood Development : Investing in Young Children for High Returns - Denboba, Amina D. (World Bank, Washington, DC, 2015)
Investing in young children is one of the best investments that countries can make. A child s earliest years present a unique window of opportunity to address inequality, break the cycle of poverty, and improve a wide range of outcomes later in life. Recent brain research suggests the need for holistic approaches to learning, growth, and development, recognizing that young children s physical and intellectual well-being, as well as their socio-emotional and cognitive development, are interrelated. To fully benefit from future opportunities in life and become productive members of society, by the end of early childhood, young children must be: healthy and well-nourished; securely attached to caregivers; able to interact positively with families, teachers, and peers; able to communicate in their native language; and ready to learn throughout primary school. This document draws on these existing frameworks and broad evidence on the impacts of ECD interventions. It summarizes some of the existing literature on this topic with the aim to identify key interventions needed for children. The document is intended to provide an easily accessible introduction to interventions and integrated services that could help policymakers and practitioners think about how to effectively invest in ECD. In addition to identifying key interventions, the document outlines four principles that can help countries design and implement strong ECD policies and programs. Countries should: (i) prepare an ECD diagnostic and strategy; (ii) implement widely through coordination; (iii) create synergies and cost savings through integrated interventions; and (iv) monitor, evaluate, and scale up successful interventions. In terms of interventions, within the ECD period, 25 key interventions are identified as essential for a child s growth and development. For each intervention, illustrative costs and impacts are provided. These are based on existing evidence and are only intended to be indicative. The document suggests that these interventions can be delivered through five integrated packages at different stages in a child s life. The five packages of interventions include: (a) the family support package, which should be provided throughout the ECD period, (b) the pregnancy package, (c) the birth package (from birth to six months), (d) the child health and development package, and (e) the preschool package.